A guide to selecting high-performing antibodies for Stearoyl-CoA desaturase (SCD1) (UniProt ID: O00767) for use in western blot, immunoprecipitation, and immunofluorescence [version 2; peer review: 1 approved, 2 approved with reservations] - Carl Laflamme; Vera Ruíz Moleón; Sara González Bolívar; Riham Ayoubi; Charles Alende; Maryam Fotouhi (F1000Research)
The enzyme stearoyl-CoA desaturase (SCD1) is a modulator of lipid metabolism by catalyzing the biosynthesis of mono-unsaturated fatty acids from saturated fatty acids. Understanding the specific mechanisms by which SCD1 plays in health and disease can provide novel insides in therapeutic targets, a process that would be facilitated by the availability of high-quality antibodies. Here we have characterized nine SCD1 commercial antibodies for western blot, immunoprecipitation, and immunofluorescence using a standardized experimental protocol based on comparing read-outs in knockout cell lines and isogenic parental controls. These studies are part of a larger, collaborative initiative seeking to address antibody reproducibility issues by characterizing commercially available antibodies for human proteins and publishing the results openly as a resource for the scientific community. While use of antibodies and protocols vary between laboratories, we encourage readers to use this report as a guide to select the most appropriate antibodies for their specific needs.